2019
DOI: 10.1186/s12889-019-7625-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-term acceptability of the Woman’s Condom and influencing factors among internal migrants in China

Abstract: BackgroundThe Woman’s Condom, a newly designed condom for women, has obtained market approval in China, but it remains relatively unfamiliar to the migrant population. The aim of this study is to evaluate the short-term acceptability of the Woman’s Condom and influencing factors among internal migrants.MethodsA longitudinal study was conducted among 1800 migrants in Beijing, Chongqing, and Shanghai in China between August 2013 and August 2014.Three-level model was implemented with the Statistical Analysis Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Receiving a recommendation from a provider, friend, or family member was an important enabler for method adoption, particularly for the female condom, copper IUD, and hormonal IUD (Harris and Angel 2020;Nanda et al 2018;Gottert et al 2015;Azmat et al 2012;Boller et al 2018;Gedeon et al 2015;Eva et al 2018;FHI360 and Family Health Options Kenya 2016, 360;Danna et al 2019;POW PDP 2015). As expected, user satisfaction with a chosen method was linked to the continuation of most methods (RamaRao et al 2018;Miller et al 2018;Nanda et al 2018;Somesh Kumar et al 2014;Ting, Wong, and Tnay 2018;Agot et al 2019;Minnis et al 2018;Ndegwa et al 2014;Eva et al 2018;Kakaire et al 2016;Azmat et al 2012;FHI 360, SFH Nigeria, and PSI 2020a;Blumenthal et al 2016;Scavuzzi, Souza, and Amorim 2016;Van Dijk et al 2013;Santibenchakul and Jaisamrarn 2016;Sodje et al 2016;Wanyenze et al 2011;Bharadwaj 2015;Pandit et al 2014;Joanis et al 2011;Dam et al 2015;Radwan et al 2019;Park, Nguyen, and Ngo 2011;Ezegwui et al 2013;Wu et al 2019;Moagi, Snyman, and Makin 2019;Das et al 2016).…”
Section: mentioning
confidence: 73%
“…Receiving a recommendation from a provider, friend, or family member was an important enabler for method adoption, particularly for the female condom, copper IUD, and hormonal IUD (Harris and Angel 2020;Nanda et al 2018;Gottert et al 2015;Azmat et al 2012;Boller et al 2018;Gedeon et al 2015;Eva et al 2018;FHI360 and Family Health Options Kenya 2016, 360;Danna et al 2019;POW PDP 2015). As expected, user satisfaction with a chosen method was linked to the continuation of most methods (RamaRao et al 2018;Miller et al 2018;Nanda et al 2018;Somesh Kumar et al 2014;Ting, Wong, and Tnay 2018;Agot et al 2019;Minnis et al 2018;Ndegwa et al 2014;Eva et al 2018;Kakaire et al 2016;Azmat et al 2012;FHI 360, SFH Nigeria, and PSI 2020a;Blumenthal et al 2016;Scavuzzi, Souza, and Amorim 2016;Van Dijk et al 2013;Santibenchakul and Jaisamrarn 2016;Sodje et al 2016;Wanyenze et al 2011;Bharadwaj 2015;Pandit et al 2014;Joanis et al 2011;Dam et al 2015;Radwan et al 2019;Park, Nguyen, and Ngo 2011;Ezegwui et al 2013;Wu et al 2019;Moagi, Snyman, and Makin 2019;Das et al 2016).…”
Section: mentioning
confidence: 73%
“…27 Demand generation efforts focused on LMIC markets primarily in sub-Saharan Africa and China (because the manufacturer was based there and wanted to build the domestic market). Early market introduction studies [28][29][30] in both of these countries as well as Zambia 31 confirmed that consumers liked the product. However, most female condom products are purchased by international procurement for distribution in LMICs.…”
Section: Challenges and Lessons Learntmentioning
confidence: 90%